2003
DOI: 10.1107/s1600536803025224
|View full text |Cite
|
Sign up to set email alerts
|

Glycoluril diamide dihydrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 203 K Mean '(C±C) = 0.001 A Ê Disorder in solvent or counterion R factor = 0.034 wR factor = 0.098 Data-to-parameter ratio = 14.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…As part of this study of cucurbituril chemistry and the preparation of new cucurbiturils, we synthesized the title compound, (I). Although many crystal structures of glycoluril and its derivatives have been reported to date (Xu et al, 1994;Wu et al, 2002;Fettinger et al, 2003Fettinger et al, , 2004Creaven et al, 2004), and and co-workers have reported the co-crystallized structure of the title organic compound with pyridine (Moon et al, 2003), this is the ®rst report of the new and interesting structure of (I).…”
Section: Commentmentioning
confidence: 83%
“…As part of this study of cucurbituril chemistry and the preparation of new cucurbiturils, we synthesized the title compound, (I). Although many crystal structures of glycoluril and its derivatives have been reported to date (Xu et al, 1994;Wu et al, 2002;Fettinger et al, 2003Fettinger et al, , 2004Creaven et al, 2004), and and co-workers have reported the co-crystallized structure of the title organic compound with pyridine (Moon et al, 2003), this is the ®rst report of the new and interesting structure of (I).…”
Section: Commentmentioning
confidence: 83%